Importancia de la nutrición en el desempeño escolar de los estudiantes de tercer año paralelo “a” de la escuela Isidro Ayora del cantón Latacunga en el periodo académico 2013-2014 - Amores Defáz, Paulina Natali (2015)
The present investigation was carried out in to Isidro Ayora school during academic period 2013-2014 ; where educational community participated, taking into account that nutrition plays a very important roll inside of teaching - learning process and especially in the students school performance. There fore a survey was made to know lifestyles, particularly nutritious habits, that takes each one of the children,where it confirmed that the students didn't have knowledge about the nutrition importance and its consequences of the low school performance, based to the used instrument, it allowed to give a standard to elaborate a proposal whose principal objective was to carry out a training program directed to the family parents of the third year of the basic education parallel “A” that it has as base; the importance of the nutrition in the children , and the protein, foods that they should contain in their lunchbox school for their healthy growth….